2013
DOI: 10.2337/db12-0354
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Specific Vascular Endothelial Growth Factor Deletion Induces Muscle Capillary Rarefaction Creating Muscle Insulin Resistance

Abstract: Muscle insulin resistance is associated with a reduction in vascular endothelial growth factor (VEGF) action and muscle capillary density. We tested the hypothesis that muscle capillary rarefaction critically contributes to the etiology of muscle insulin resistance in chow-fed mice with skeletal and cardiac muscle VEGF deletion (mVEGF−/−) and wild-type littermates (mVEGF+/+) on a C57BL/6 background. The mVEGF−/− mice had an ∼60% and ∼50% decrease in capillaries in skeletal and cardiac muscle, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 57 publications
3
105
0
1
Order By: Relevance
“…In the insulin-resistant states, VEGF actions in muscle vascular beds are impaired, which triggers muscle capillary regression (17,20). This is consistent with the observation that musclespecific VEGF deletion induces muscle capillary rarefaction and muscle insulin resistance (8,41).…”
supporting
confidence: 74%
“…In the insulin-resistant states, VEGF actions in muscle vascular beds are impaired, which triggers muscle capillary regression (17,20). This is consistent with the observation that musclespecific VEGF deletion induces muscle capillary rarefaction and muscle insulin resistance (8,41).…”
supporting
confidence: 74%
“…In the present study, an increase in VEGF mRNA expression in skeletal muscle was observed following both LBH and TH, demonstrating that this central proangiogenic factor might also mediate the angiogenic response to heat therapy in skeletal muscle. VEGF regulates basal and exercise training-induced increases in skeletal muscle capillarization (80), and muscle-specific deletion of this molecule leads to capillary rarefaction (3,52) and nearly abolishes exerciseinduced capillary growth (53).…”
Section: Skeletal Muscle Angiogenic Signalingmentioning
confidence: 99%
“…Although defective glucose transport, mediated by GLUT4, is central to the development of skeletal muscle insulin resistance (40), it is recognized that diminished microvascular recruitment (8) and skeletal muscle rarefaction (5) are also important contributing factors.…”
mentioning
confidence: 99%